Gestão do patrimônio genético e do conhecimento tradicional associado à flora- perspectivas, oportunidades e lacunas - Hirdes, Yasmin Tavares (2025)
Brazil, the country with the greatest biodiversity on the planet, is home to precious natural resources for the well-being of society. Historically, the use of nature has been predatory and unequal. The concentration of profits obtained from nature and the disrespect for the guardians of socio-biodiversity are elements that permeate the history of this land. The legal regulation on the subject of access to biodiversity in the country was also constructed in a partial manner and favored the interests of pharmaceutical, cosmetic, and other related industries. It is in this context that this research sought to understand the panorama of access to the floristic component of the Cerrado, for the purposes of research and technological development. The work evaluated public data from the National Genetic Heritage Management System related to plants of the Cerrado, with the aim of contributing to the expansion of knowledge about the plant diversity of the Cerrado and its applications. Among the records made between 2017 and 2023, 5,472 records of access to genetic heritage and genetic heritage and associated traditional knowledge, 482 shipments, and 190 notifications of finished products indicating samples from the Cerrado were identified. In addition, public data from 31 Non-Monetary Benefit Sharing Agreements (ARB-NM), proposed by seven companies, were evaluated. ARB-NMs mainly benefit national public research and development institutions (29%) and are being implemented mainly in the Atlantic Forest (32.3%), Amazon (29%), and Cerrado (16.1%). Finally, the study sought to present the bottlenecks arising from the implementation of Law 13.123/2015, with a view to presenting possible paths for biodiversity conservation, which respect the guardians of biodiversity, within a historical scenario of threat to their territories and knowledge.